DETERMINANTS OF PROFITABILITY AND CAPITAL STRUCTURE IN KOMPAS100 INDEX COMPANIES YEAR 2016-2020 - Juniar Vina; Achmad Tavip Junaedi; Harry Patuan Panjaitan (Journal of Applied Business and Technology, 2021)
This study aims to analyze how the influence of Asset Growth, Asset Structure, Company Size, Business Risk, Non Debt Tax Shield on Capital Structure and Profitability. The sampling technique in this study was purposive sampling method with a population of 100 companies and a sample of 76 companies and the data analysis techniques used were Descriptive Analysis, Multicollinearity Test, Coefficient of Determination Test, Path Analysis. The Independent Variables are Capital Structure and Profitability. The results of this study indicate that asset growth has no effect on profitability, asset structure has a positive effect on profitability, firm size has a positive effect on profitability, business risk has no effect on profitability, asset growth has a negative effect on capital structure, asset structure has a positive effect on capital structure, size the company has no effect on capital structure, business risk has a positive effect on capital structure, Non Debt Tax Shield has a negative effect on capital structure, profitability has a negative effect on capital structure.